The Students' Mistakes In Using Simple Past Tense For Writing Short Sentences - Helmi (Universitas Achmad Yani Banjarmasin, 2021)
Students’ Mistakes in using simple past tense for writing short sentences at elementary teacher department of faculty of teachers’ training and education of Achmad Yani University. The objective of this study is to analyze the students’ mistakes in writing short sentences based on in simple past tense. The scope of the research is focused on one tenses namely simple past tense. Research method was used in this research is descriptive qualitative method. Based on the result of the research, the researcher could conclude that most of subject or sample of the research did mistakes in misinformation because they write wrong in grammatical form and made the sentences were incorrect.